Impella Induced Massive Hemolysis: Reemphasizing Echocardiographic Guidance for Correct Placement - Shaun Cardozo; Tasneem Ahmed; Kevin Belgrave (Case Reports in Cardiology)
The Impella LP 2.5 (Abiomed, Danvers, MA) has been a tool of use for high risk coronary procedures and for cardiogenic shock. As with any invasive or intracardiac device, improper placement can result in disastrous complications. Hemolytic anemia secondary to Impella implantation is one of the documented complications. However, cases of severe hemolytic anemia are rare in the literature. Proven imaging modalities like ultrasound need to be used to guide proper placement. We present a case of device induced severe hemolysis due to Impella insertion and the need to use ultrasound guidance to avoid such an unnecessary complication.